Da crise de representatividade e das manifestações de junho de 2013 à regulamentação do direito de participação social - Sichonany Neto, Saul de Oliveira (2015)
The manifestations that took place in Brazil throughout June 2013 have made their way into the history of the country. Protests called by virtue of the increase in public transport fares, specially in the city of São Paulo, spread to hundreds of cities, leading millions of people to the streets, with the expansion of the demand for guidelines. Politicians, state institutions and politics itself were targeted by protesters who have clearly shown they do not feel represented by elected politicians. These manifestations of rejection lead to the conclusion that the crisis of representation, faced by many democracies around the globe, is felt daily by people. Besides, a deficit of participation is also notable, i.e., there is no place or encouragement for people to participate in state decisions. In this context, politicians were surprised by the magnitude of the protests, not knowing how to interpret the claims from the streets in first place. It was necessary to provide answers, and President Dilma Rousseff interpreted the events as a request for greater participation. Less than a year after the June events, the Presidency of the Republic published Act 8.243/2014, which established the National Policy for Social Participation and the National Social Participation System. The Act has been criticized, but also supported. In the same sense of criticism, Legislative Act Projects with the Congress were presented in order to halt the effects of the Presidential Act. Hence, this research is inserted in the context of the crisis of representation and the expansion of popular participation channels within the state institutions. The objective is to verify whether and to what extent Act 8.243/2014 was influenced by the events of June 2013, as well as to evaluate the projects that wish to overthrow the Act, in order to verify the constitutionality of such rule. Therefore, the hypothetical-deductive method of approach has been applied and regarding the procedure, the methods were the case study and the functionalist. It was concluded that the publication of Act 8.243/2014 has relationships with the events that occurred in June 2013. In addition, the debate established by the critics of the Act is political, since the legal arguments for restraining its effects do not thrive. It is fighting for positions of power instead of a strictly legal debate.